CDS spreads and systemic risk: A spatial econometric approach - Sebastian Keiler; Armin Eder (Deutsche Bundesbank, 2013)
This study applies a novel way of measuring, quantifying and modelling the systemic risk within the financial system. The magnitude of risk spill over effects is gauged by introducing a specific weighting scheme. This approach originally stems from spatial econometrics. The methodology allows for a decomposition of the credit spread into a systemic, systematic and idiosyncratic risk premium. We identify considerable risk spill overs due to the interconnectedness of the financial institutes in the sample. In stress tests, up to one fifth of the CDS spread changes are owing to financial contagion. These results also give an alternative explanation for the nonlinear relationship between a debtor's theoretical probability of default and the observed credit spreads - known as the credit spread puzzle.
Keywords: C21; G12; G18; G21; 330; systemic risk; financial contagion; spatial econometrics; CDS spreads; government policy and regulation